Empowering Disabled Economic MaqÄá¹£id Asy-SyarÄ«â€™ah Perspective in UD. Mutiara Handycraft Karangsari Buayan Kebumen Central Java - Faozan, Akhmad (Ijtim?'iyya: Journal of Muslim Society Research, 2019)
This article discusses the economic empowerment among the disabled in UD Mutiara Handycraft Karangsari Buayan, Kebumen Regency, Central Java seen from the maqa?s?id al-syari??ah perspective. The economic empowerment aims at empowering the disabled to be more creative and have a better living standard in economic and social aspects. Through this program, they are expected to produce work that can make money, have jobs and be more confident in communicating and interacting with other people. The disabled economic empowerment is very important in order to improve their ability and skills so that they can carry out economic activities as normal people can do. Islamic law has several objectives, namely protecting the religion (h?ifz?u ad-di?n), protecting the wealth (h?ifz?u al-ma?l), protecting the soul (h?ifz?u an-nafs), protecting the generation (h?ifz?u an-nasl) and protecting the mind (h?ifz?u al-?aql). Some scholars suggested the sixth goal of Islamic law, i.e. protecting the honor (h?ifz?u al-?ard?). These objectives are well-known by the term maqa?s?id al-syari??ah. After collecting the data, the author analyzed them using theory of maqa?s?id al-syari??ah. The results of this study shows that the economic empowerement of the disable in UD Mutiara Handycraft suits the theory of maqa?s?id al-syari??ah, which includes protecting the religion, the wealth, the soul, the generation, the soul and the honor.